One-year pulmonary impairment after severe COVID-19: a prospective, multicenter follow-up study - Faverio, Paola; Luppi, Fabrizio; Rebora, Paola; D’Andrea, Gabriele; Stainer, Anna; Busnelli, Sara; Catalano, Martina; Modafferi, Giuseppe; Franco, Giovanni; Monzani, Anna; Galimberti, Stefania; Scarpazza, Paolo; et al. (Respiratory research, 2022)
Background Long-term pulmonary sequelae following hospitalization for SARS-CoV-2 pneumonia is largely unclear. The aim of this study was to identify and characterise pulmonary sequelae caused by SARS-CoV-2 pneumonia at 12-month from discharge. Methods In this multicentre, prospective, observational study, patients hospitalised for SARS-CoV-2 pneumonia and without prior diagnosis of structural lung diseases were stratified by maximum ventilatory support (“oxygen only”, “continuous positive airway pressure (CPAP)” and “invasive mechanical ventilation (IMV)”) and followed up at 12 months from discharge. Pulmonary function tests and diffusion capacity for carbon monoxide (DLCO), 6 min walking test, high resolution CT (HRCT) scan, and modified Medical Research Council (mMRC) dyspnea scale were collected. Results Out of 287 patients hospitalized with SARS-CoV-2 pneumonia and followed up at 1 year, DLCO impairment, mainly of mild entity and improved with respect to the 6-month follow-up, was observed more frequently in the “oxygen only” and “IMV” group (53% and 49% of patients, respectively), compared to 29% in the “CPAP” group. Abnormalities at chest HRCT were found in 46%, 65% and 80% of cases in the “oxygen only”, “CPAP” and “IMV” group, respectively. Non-fibrotic interstitial lung abnormalities, in particular reticulations and ground-glass attenuation, were the main finding, while honeycombing was found only in 1% of cases. Older patients and those requiring IMV were at higher risk of developing radiological pulmonary sequelae. Dyspnea evaluated through mMRC scale was reported by 35% of patients with no differences between groups, compared to 29% at 6-month follow-up. Conclusion DLCO alteration and non-fibrotic interstitial lung abnormalities are common after 1 year from hospitalization due to SARS-CoV-2 pneumonia, particularly in older patients requiring higher ventilatory support. Studies with longer follow-ups are needed.